KUALITAS PELAYANAN PARKIR DI TEPI JALAN UMUM KOTA YOGYAKARTA - Ilosa, Abdiana (Natapraja, 2016)
Starting in 2010 the Government of Yogyakarta, according to regional regulation about parking and levy on the edge of public street parking. This policy expected to increase parking levy’s revenues, more secure services and convenient parking, and traffic flows smoothly. This research used qualitative descriptive method. This research analyzed qualitative indicators of quality of service: 1) tangible 2) reliability; 3) transaparant and 4) security. This research found that public street parking less well and yet according to the wishes of the community. This is because the layout of the parking spaces are not in place that interfere with the capacity of highways and disrupting the pedestrian capacity. Then the rates charged by parking operator which do not comply with official rates. Human resources of Transportastion Department that monitor directly into the field just a pick up that add up to 12 people to keep an eye on the parking lot 900 people outside the parking operators so ineffective, so that a parking lot of cheating. Keywords: Parking Service Quality, Parking Space, Lack of Human Resource.